Molecular characterization of quorum sensing and quorum quenching mesophilic microorganisms isolated from ulu slim hot spring / Hong Kar Wai - Hong, Kar Wai (2014)
A wide range of Proteobacteria are known to produce signalling molecules, such as N-acyl-homoserine lactones (AHLs) to regulate genes expression in a populationdependent manner, thereby enabling group behavior acted in unison. This mechanism of cell-to-cell communication is known as quorum sensing (QS). In a polymicrobial community, while some bacteria are communicating with neighboring cells, others are interrupting the communication, and the interruption of communication is known as quorum quenching (QQ). In this study, the production and degradation of AHLs by bacteria isolated from Ulu Slim Hot Spring were investigated. Pseudomonas aeruginosa and Methylobacterium sp. were found to synthesize AHL in this study. Significant QQ activity was discovered among Bacillus megaterium, Gordonia sp., P. aeruginosa, Pseudomonas otitidis, Roseomonas sp. and Rhodotorula mucilaginosa using triple quadrupole liquid chromatography mass spectrometry (LC/MS/MS-QQQ). Degradation of AHLs by Gordonia sp. and Rhodotorula (a fungus) was documented for the first time in this study. Selected bacterial isolates have been isolated and identified using both MicroflexTM LT MALDI-TOF approach as well as 16S rRNA gene sequencing approach. The bacterial isolates include Kocuria rhizophila CN12, Stenotrophomonas maltophila F2, Chelatococcus sp. M3, Providencia rettgeri M22, Dermacoccus nishinomiyaensis M25, Schineria sp. M27, Cronobacter sakazakii M30, Exiguobacterium aurantiacum M31, Brevibacterium casei M40, Proteus mirabilis M48 and Micrococcus luteus M71.